2007
DOI: 10.1111/j.1469-8749.2006.tb01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Gross and fine motor function and accompanying impairments in cerebral palsy

Abstract: The aim of this study was to describe and analyze gross and fine motor function and accompanying neurological impairments in children with cerebral palsy (CP) born between 1991 and 1998 in western Sweden. A population‐based study comprised 411 children with a diagnosis of CP ascertained at 4 to 8 years of age. Gross Motor Function Classification System (GMFCS) levels were documented in 367 children (205 males, 162 females). Bimanual Fine Motor Function (BFMF) classification levels of 345 of the children and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
86
6
13

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 33 publications
18
86
6
13
Order By: Relevance
“…As for the relation between body topography and motor levels, most hemiplegic children were predominantly motor level I, which has also been found in other studies [17][18][19]25 . In this study there was only one child with hemiplegics cP different from level I and she was classified in Motor level III according to the GMFcS.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…As for the relation between body topography and motor levels, most hemiplegic children were predominantly motor level I, which has also been found in other studies [17][18][19]25 . In this study there was only one child with hemiplegics cP different from level I and she was classified in Motor level III according to the GMFcS.…”
Section: Discussionsupporting
confidence: 61%
“…The child was 8 months old and had late development; it is possible that such condition reaches the lowest lower limbs because of its neurological maturation. himmelmann et al 25 found out cases of hemiplegia in all motor levels; Beckung et al 19 established that the cases varied between levels I and IV; howard et al 16 found levels I, II, III and V and Voorman et al 18 classified the cases under levels I, II and III. diplegic children in this study were similar (with no significant difference) in the first four levels and there were no examples of level V; in their study Voorman et al 18 had the same results and only 3 cases (6.4%) were level V. In their study himmelmann et al 25 had diplegic children in all levels, most of them were level II (37.5%) and only 4.9% of the children were classified in level V. Similar results were found in the study of Beckung et al 19 in which they observed that most children were classified in the first two levels while only 4% were classified in level V. The results in the study of howard et al 16 were very similar in the first three levels; only 4 cases (5%) were level IV and no diplegic children were level V.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,6 Because the diagnosis of CP is based on clinical features but does not describe all the consequences of the disability, 7 the diagnosis must be used in combination with functional classifications. [8][9][10] Using a five-level approach, the Communication Function Classification System (CFCS) can classify the everyday communication of a person with CP, including communication with AAC systems. 11 Distinctions between the five levels of the CFCS are based on important aspects of functional communication, namely the performance of the sender and receiver roles, the pace of the conversation, and the type of communication partner.…”
Section: Resultsmentioning
confidence: 99%
“…[5] Less research has been carried out on the epidemiology of CP in children of NBW than in those of very low birthweight (< 1500 g). As the number and severity of impairments increase with increasing gestational age [6,7] and birthweight, [8] the type of brain lesion among term or NBW children tends to exhibit a different pattern to that of preterm or low birthweight births. [9][10][11] Time trends for CP prevalence in NBW children vary across studies.…”
Section: Introductionmentioning
confidence: 99%